The Effect of Estradiol and Progesterone on Toll Like Receptor Gene Expression in A Human Fallopian Tube Epithelial Cell Line - Zandieh, Zahra (Cell J, 2016)
OBJECTIVE: Toll like receptors (TLRs) are one of the main components of the innate im- mune system. It has been reported that expression of these receptors are altered in the female reproductive tract (FRT) during menstrual cycle. Here we used a fallopian tube epithelial cell line (OE-E6/E7) to evaluate the effect of two sex hormones in modulating TLR expression. MATERIALS AND METHODS: In this experimental study, initially TLR gene expression in OE- E6/E7 cells was evaluated and compared with that of fallopian tube tissue using quanti- tative real time-polymerase chain reaction (qRT-PCR) and immunostaining. Thereafter, OE-E6/E7 cells were cultured with different concentrations of estradiol and progesterone, and combination of both. qRT-PCR was performed to reveal any changes in expression of TLR genes as a result of hormonal treatment. RESULTS: TLR1-10 genes were expressed in human fallopian tube tissue. TLR1-6 genes and their respective proteins were expressed in the OE-E6/E7 cell line. Although estradiol and progesterone separately had no significant effect on TLR expression, their combined treatment altered the expression of TLRs in this cell line. Also, the pattern of TLR expres- sion in preovulation (P), mensturation (M) and window of implantation (W) were the same for all TLRs with no significant differences between P, M and W groups. CONCLUSION: These data show the significant involvement of the combination of es- tradiol and progesterone in modulation of TLR gene expression in this human fal- lopian tube cell line. Further experiments may reveal the regulatory mechanism and signalling pathway behind the effect of sex hormones in modulating TLRs in the hu- man FRT.